Mitigation of heave response of semi-submersible platform (SSP) using tuned heave plate inerter (THPI) - Ma, R.; Bi, Kaiming; Hao, Hong (Pergamon, 2018)
The undesirable motions resulting from wave loading can lead to the long-term fatigue damage or even catastrophic sinking of offshore semi-submersible platforms (SSP). It is therefore by all means necessary to suppress the excessive vibrations of SSP. Many methods have been proposed to mitigate the heave motion of offshore platforms, such as using a fixed heave plate (FHP) to increase the draft and damping of the system, or adopting a tuned heave plate (THP) to form a tuned mass damper (TMD) system. In this paper, a novel inerter-based control system, namely a tuned heave plate inerter (THPI), is proposed for control of SSP heave vibrations. In this system, an inerter device, which can transform the linear motion into the high-speed rotational motion and thus significantly amplifies the physical mass of the system, is added to the THP to further improve the performance of conventional THP. Analytical studies are performed to investigate the effectiveness of the proposed method. The mean square heave motions of SSP without control device and with FHP, THP and THPI are stochastically formulated, and the optimal design parameters for THP and THPI are derived. Parametric studies are conducted to investigate the influences of the size and original depth of heave plate on the optimal performances of FHP, THP and THPI. Finally, a novel waterwheel inerter is developed to realize the suggested device. The analytical results show that THPI is more effective to mitigate the heave motion of SSP compared to the conventional methods, and the novel waterwheel inerter is capable of generating a large apparent mass by using a small waterwheel.